Non Performing Assets: A Burden on Banking Sector (An Assessment of Indian Commercial Banks’ Profitability) - Dr. Naina Hasija (International Journal of Engineering and Management Research, 2019)
After the evolution of new Industrial Policy 1991, banking system reforms became an important issue for the government. During this the reforms laid down by the Shri Narasimhan Rao Committee became quit important. It was at this time that the banking system was drastically transformed. These reforms adopted the international best practices to strengthen the functioning of banking industry. Many of these proposed reforms were implemented in the hopes of enhancing bank overall efficiency and lowering non-performing assets (NPA). The banks' profitability and financial efficiency would also improve as a result of this. For the purposes of this study, individual private sector banks, nationalised banks, and SBI and its affiliates were considered. The research is based on secondary data from the Reserve Bank of India's website for the years 2010 to 2017. The purpose of this research is to determine how banks have contributed to the growing threat and what the banking industry's trend has been in regards to these low-quality loans. The author has also attempted to research and analyse RBI's proposal to implement Basel III norms in the banking sector beginning in January 2013, as formulated by the Bank for International Settlements (BIS) in consultation with central banks operating in a number of countries around the world in their respective economies and following sound financial and operational policies.